Interpreting for LGBTIQ+ asylum seekers in the Netherlands: challenges and policy recommendations - Crezee, Ineke H.; Monzó-Nebot, Esther; Ramirez, Elba; Sanders, Jona (Frontiers in Communication, 2025)
LGBTIQ+ asylum seekers face unique challenges in proving their claims, as their identities are often criminalized or stigmatized in their home countries. Asylum processes rely heavily on credibility assessments, where interpreters play a crucial role in communication. Common issues in interpreter-mediated asylum interviews include lack of specialized training, linguistic barriers, cultural biases, confidentiality concerns, and structural undervaluation of interpreters. In the Netherlands, Work Instruction 2019/17 provides guidelines for assessing LGBTIQ+ claims incorporating international recommendations, but gaps persist in interpreter selection, training, and oversight. This review identifies best practices, including comprehensive interpreter training, trauma-informed approaches, and standardized ethical guidelines. Policy recommendations are suggested, emphasizing the need for clearer protocols, ongoing professional development, and institutional recognition of interpreters’ impact on asylum outcomes.